2022
DOI: 10.1308/rcsann.2021.0078
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D repletion in primary hyperparathyroid patients undergoing parathyroidectomy leads to reduced symptomatic hypocalcaemia and reduced length of stay: a retrospective cohort study

Abstract: Introduction Vitamin D deficiency co-exists with and can confuse the diagnosis of primary hyperparathyroidism (PHPT). Vitamin D replete (VDR) status may prevent significant postparathyroidectomy hypocalcaemia; however, reports from previous studies are conflicting. This study aimed to assess differences in early and/or late postoperative hypocalcaemia and length of stay (LOS) postparathyroidectomy between VDR and vitamin D non-replete (VDNR) PHPT patients. Methods This was a retrospective cohort study of a pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
0
3
0
3
Order By: Relevance
“…У наших пациентов, принимавших колекальциферол, статистически значимо реже наблюдалась послеоперационная гипокальциемия по сравнению с пациентами, не принимавшими данный препарат. Результаты трех различных исследований сходны с нашими данными и подтверждают протективную роль нормальной концентрации 25(OH)D [ 7 ][ 21 ][ 22 ]. Исследование, проведенное Acharya и соавт., показало, что насыщение витамином D является значимым фактором, влияющим на симптомы гипокальциемии.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…У наших пациентов, принимавших колекальциферол, статистически значимо реже наблюдалась послеоперационная гипокальциемия по сравнению с пациентами, не принимавшими данный препарат. Результаты трех различных исследований сходны с нашими данными и подтверждают протективную роль нормальной концентрации 25(OH)D [ 7 ][ 21 ][ 22 ]. Исследование, проведенное Acharya и соавт., показало, что насыщение витамином D является значимым фактором, влияющим на симптомы гипокальциемии.…”
Section: Discussionunclassified
“…Исследование, проведенное Acharya и соавт., показало, что насыщение витамином D является значимым фактором, влияющим на симптомы гипокальциемии. Полученные результаты свидетельствуют о наличии статистически значимой ассоциации между насыщением витамином D и развитием гипокальциемии (ОШ=4,9 [ 95% ДИ: 1,8–13,7]) [ 7 ]. В исследовании Unsal и соавт.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…It is important to note that patients in the study received calcitriol after surgery as part of standard postoperative care [ 48 ]. In a retrospective cohort study, it was found that vitamin D repletion in PHPT patients undergoing parathyroidectomy decreases hypocalcemia and reduces the length of hospital stay [ 61 ].…”
Section: Supplementation Of Vitamin D In Phptmentioning
confidence: 99%
“…The occurrence of these symptoms is the result of a rapid decline in PTH levels after surgery, after a long period of high PTH levels in PHPT ( 5 ). Vitamin D deficiency in preoperative patients leads to an increased probability of postoperative hypocalcemia ( 6 ).…”
Section: Introductionmentioning
confidence: 99%